2022-VA-920-ESGO Adrenal gland recurrent cervical cancer treated by minimally invasive approach. (20th October 2022) - Rosati, Andrea; Certelli, Camilla; Scaglione, Giulia; Baroni, Alessandro; Federico, Alex; Capomacchia, Filippo Maria; Greco, Pierfrancesco; Fanfani, Francesco; Scambia, Giovanni; Gallotta, Valerio
Abstract : Introduction/Background: Recurrence of disease represents a clinical challenge in cervical cancer patients and the choice of the best treatment depends on previous therapy and site of recurrent tumor. The paraortic lymph nodes and the lungs were the extrapelvic areas more frequently involved, whereas adrenal gland involvement is rarely reported. Some reports confirmed the survival benefit of secondary radical surgery in confined recurrence, although this finding has been rarely investigated in the literature with only a few case series reported mostly focusing on lung metastases. Methodology: Here a case of isolated adrenal gland cervical cancer recurrence in a 62-year-old woman is presented. Preoperative computed and emission tomography scans detected a nodule of 26 mm with increased uptake involving the medial lip of the right adrenal gland and a lymph node of 8 mm behind the inferior vena cava. A retrocaval lymphadenectomy and right adrenalectomy was performed. In this video we showed a minimally invasive approach tailored on the patient disease with the help of intraoperative ultrasound. Results: We reached a residual tumor of zero with good operation times. No intra or postoperative complications occurred. Final histology confirmed the metastatic involvement of both the adrenal gland and the retrocaval lymph node by an undifferentiated carcinoma. After a multidisciplinary board evaluation, the patient underwent chemotherapy. Conclusion: Minimally invasive surgery in selected patients with isolated extrapelvic cervical cancer recurrence is feasible and safe. Since radicality may be guaranteed by intraoperative imaging such as ultrasound, surgery can be tailored on the single patient and disease.